Nitrate determines the bacterial habitat specialization and impacts microbial functions in a subsurface karst cave - Liu, Xiaoyan; Wang, Hongmei; Wang, Weiqi; Cheng, Xiaoyu; Wang, Yiheng; Li, Qing; Li, Lu; Ma, Liyuan; Lu, Xiaolu; Tuovinen, Olli H. (Frontiers in Microbiology, 2023)
Karst caves are usually considered as natural laboratories to study pristine microbiomes in subsurface biosphere. However, effects of the increasingly detected nitrate in underground karst ecosystem due to the acid rain impact on microbiota and their functions in subsurface karst caves have remained largely unknown. In this study, samples of weathered rocks and sediments were collected from the Chang Cave, Hubei province and subjected to high-throughput sequencing of 16S rRNA genes. The results showed that nitrate significantly impacted bacterial compositions, interactions, and functions in different habitats. Bacterial communities clustered according to their habitats with distinguished indicator groups identified for each individual habitat. Nitrate shaped the overall bacterial communities across two habitats with a contribution of 27.2%, whereas the pH and TOC, respectively, structured bacterial communities in weathered rocks and sediments. Alpha and beta diversities of bacterial communities increased with nitrate concentration in both habitats, with nitrate directly affecting alpha diversity in sediments, but indirectly on weathered rocks by lowering pH. Nitrate impacted more on bacterial communities in weathered rocks at the genus level than in sediments because more genera significantly correlated with nitrate concentration in weathered rocks. Diverse keystone taxa involved in nitrogen cycling were identified in the co-occurrence networks such as nitrate reducers, ammonium-oxidizers, and N2-fixers. Tax4Fun2 analysis further confirmed the dominance of genes involved in nitrogen cycling. Genes of methane metabolism and carbon fixation were also dominant. The dominance of dissimilatory and assimilatory nitrate reduction in nitrogen cycling substantiated nitrate impact on bacterial functions. Our results for the first time revealed the impact of nitrate on subsurface karst ecosystem in terms of bacterial compositions, interactions, and functions, providing an important reference for further deciphering the disturbance of human activities on the subsurface biosphere.